Antenatal Depression and Its Correlates: A Case Control Study on Multiple Influencing Variables - Hasanah, Zumroh; Novembriani, Rizqie Putri (GLOBAL HEALTH SCIENCE GROUP, 2023)
Depression is a major global contributor to disability, particularly among women, with antenatal depression emerging as a leading source of health problems in this group. Recognizing risk factors is critical for early detection and prevention strategies. This study explores the correlation between antenatal depression and factors such as risky pregnancies, history of child abuse, financial difficulties, marital conflict, and pregnancy status in Surabaya. Method: The case-control study, which took place from May to July 2019 at Jagir and Tanah Kali Kedinding Public Health Centers, included 58 pregnant women. The findings indicate a strong link between antenatal depression and high-risk pregnancies. When additional factors are taken into account, characteristics such as financial difficulties, pregnancy status, marital conflict, and a history of child abuse may lose significance. Caution is urged when interpreting these findings, emphasizing the importance of considering the clinical situation